Technological Change as a Mediator of Employee Competency Profiling in Selected Industries in Kuching, Sarawak: A Structural Equation Modeling Approach - Nadri Aetis Heromi, Basmawi; Hasbee, Usop (Faculty of Cognitive Sciences & Human Development UNIMAS, 2016)
This study aims to investigate competency profiling and determine if technological change act as a mediator in the relationship between the identified factors and employee competency in selected industries in Kuching, Sarawak. It is also to develop the best fit model based on the variables selected. The four identified variables are teamwork, organizational culture, change management, and technological change. The sample of this study were 302 respondents selected through a simple random sampling. The findings showed that there is a positive effect between teamwork, organizational culture, change management, and technological change as mediator towards employee competency. This study provides positive implications, such as, improving competency process in organizational setting, improving policy and related action plan regarding human resource practices on competency.